Risk Management in Village Financial Management in Village Government in North Sumatera - Oktarini Khamilah Siregar; Mohd. Abidzar Bin Zainol Abidin; Vina Arnita; Rica Cahya Amalya (International Forum of Researchers and Lecturers, 2025)
Village financial management plays a crucial role in ensuring the effective and efficient use of village funds, particularly when viewed from the perspective of risk management. Risk management in this context refers to efforts made by village governments to anticipate, identify, and address potential problems that may arise in the use of village funds. Central government policies provide an important foundation for quality planning, implementation, and supervision in village financial management. This study employs a descriptive approach to explain the challenges faced by village governments in managing finances and highlights the importance of applying risk management strategies to enhance village original income. In analyzing risks, accuracy and precision are required because the risks faced by the village government directly influence policy outcomes and ultimately affect the welfare of the community. By adopting appropriate risk management practices, village governments can mitigate financial mismanagement and improve revenue generation. One practical measure involves the application of targeted budget allocation policies, such as optimizing expenditure savings and ensuring effective absorption of funds. These strategies not only prevent misuse of resources but also promote sustainable financial growth at the village level. The implementation of village financial risk management is guided by the Minister of Villages Regulation, which serves as a formal reference for village governments in designing systems, procedures, and policies. Through the application of these guidelines, village governments are expected to achieve better financial governance, improve transparency, and strengthen accountability. Ultimately, risk management serves as an essential tool for ensuring that village financial management supports community development and enhances the welfare of rural society.